"His first word was 'cream'." The burden of treatment in pediatric atopic dermatitis—A mixed methods study. Issue 3 (21st December 2021) - O'Connor, Cathal; Dhonncha, Eilis Nic; Murphy, Michelle
Abstract: The burden of treatment (BOT) is the workload of health care experienced by patients with chronic conditions and consequences on well‐being. This study aimed to assess the BOT of atopic dermatitis (AD) on children and caregivers using mixed methods. The quantitative component of this mixed methods study involved the Treatment Burden Questionnaire. The qualitative component involved interviews with parents of children with moderate–severe AD. The questionnaire was completed by 168 parents; 32.1% had mild AD, 39.9% had moderate AD, and 28% had severe AD. The average burden score was 3.5 (out of 10). Average burden scores were low in mild AD (1.0 out of 10) and were proportionally higher in moderate (3.9 out of 10) and severe (5.8 out of 10) AD ( p < 0.001). Increased frequency of therapy had increased perceived burden. In moderate–severe AD, oral therapy was rated as less burdensome than topical therapies. Semi‐structured interviews were conducted with 15 parents of children with moderate–severe AD. Thematic analysis grouped experiences into health care burden, treatment burden, and financial burden. Insights from health care burden analysis included "mixed messages, " "treatment futility, " and "expectant resolution." Insights from treatment burden included treatment routine, schooling impact, and "topical‐sparing" with systemic treatment. Factors of financial burden included topical treatments, clothing, and health care visits. Moderate–severe AD is associated with high BOT, particularly related to topical therapies, which may be reduced by systemic treatment. All physicians treating children with AD should avoid potentially damaging communication regarding mixed messages, treatment futility, and expectant resolution.